Minimal role for the alternative pathway in complement activation by HIT immune complexes. (1st September 2022) - Barnes, Ayiesha P.; Khandelwal, Sanjay; Sartoretto, Simone; Myoung, Sooho; Francis, Samuel J.; Lee, Grace M.; Rauova, Lubica; Cines, Douglas B.; Skare, Jon T.; Booth, Charles E.; Garcia, Brandon L.; Arepally, Gowthami M.
Abstract: Background: Anti‐platelet factor 4 (PF4)/heparin immune complexes that cause heparin‐induced thrombocytopenia (HIT) activate complement via the classical pathway. Previous studies have shown that the alternative pathway of complement substantially amplifies the classical pathway of complement activation through the C3b feedback cycle. Objectives: These studies sought to examine the contributions of the alternative pathway to complement activation by HIT antibodies. Methods: Using IgG monoclonal (KKO) and/or patient‐derived HIT antibodies, we compared the effects of classical pathway (BBK32 and C1‐esterase inhibitor [C1‐INH]), alternative pathway (anti‐factor B [fB] or factor D [fD] inhibitor) or combined classical and alternative pathway inhibition (soluble complement receptor 1 [sCR1]) in whole blood or plasma. Results: Classical pathway inhibitors BBK32 and C1‐INH and the combined classical/alternative pathway inhibitor sCR1 prevented KKO/HIT immune complex–induced complement activation, including release of C3 and C5 activation products, binding of immune complexes to B cells, and neutrophil activation. The alternative pathway inhibitors fB and fD, however, did not affect complement activation by KKO/HIT immune complexes. Similarly, alternative pathway inhibition had no effect on complement activation by unrelated immune complexes consisting of anti‐dinitrophenyl (DNP) antibody and the multivalent DNP‐‐keyhole limpet hemocyanin antigen. Conclusions: Collectively, these findings suggest the alternative pathway contributes little in support of complement activation by HIT immune complexes. Additional in vitro and in vivo studies are required to examine if this property is shared by most IgG‐containing immune complexes or if predominance of the classic pathway is limited to immune complexes composed of multivalent antigens.